Excited state interactions between the chiral Au38L24 cluster and covalently attached porphyrin1. Issue 22 (14th June 2015) - Varnholt, Birte; Letrun, Romain; Bergkamp, Jesse J.; Fu, Yongchun; Yushchenko, Oleksandr; Decurtins, Silvio; Vauthey, Eric; Liu, Shi-Xia; Bürgi, Thomas
<x xml:space="preserve">Abstract</x> Excited state interactions between the Au38L24 cluster and the covalently attached porphyrin molecules lead to energy transfer upon excitation.